Preparation method of NdFeB magnet
By introducing elements such as Y and Ni into the neodymium iron boron magnet and using heat-resistant polyurethane elastomer adhesive, the problems of low Curie temperature and poor heat resistance of the neodymium iron boron magnet are solved, and a higher Curie temperature is achieved and better heat resistance.
Patent Information
- Application Number
- CN202410574208.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-08
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-11-08
AI Technical Summary
The existing neodymium iron boron magnets have low Curie temperature and poor heat resistance, which limits their application in high temperature environments.
By introducing elements such as Y and Ni into the neodymium iron boron magnet components, the Curie temperature and coercivity are increased, and a synthetic heat-resistant polyurethane elastomer is used as a binder to be calendered with the surface modified magnetic powder.
The Curie temperature and coercivity of the neodymium iron boron magnet are significantly improved, the temperature coefficient is reduced, the magnetic performance is maintained, the heat resistance is improved, and the application range is expanded.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] This application is a divisional application with application number 2023114738585, application date November 8, 2023, and invention name “A method for preparing heat-resistant NdFeB magnets”. Technical Field
[0002] The invention relates to the technical field of NdFeB magnets, in particular to a method for preparing a heat-resistant NdFeB magnet. Background Art
[0003] NdFeB magnets have occupied a huge market of permanent magnet materials with their excellent magnetic properties, and are increasingly used in automotive motors, wind turbines, instrumentation and other fields. Therefore, components made of NdFeB magnets need to adapt to higher ambient temperatures. In addition, in some precision instruments and magnetic devices, when the external working environment conditions change, the magnetic field provided by the magnets is required to be stable, otherwise it will affect the accuracy and reliability of the instruments, and thus the magnets are required to have a low temperature coefficient. However, ordinary NdFeB magnets have a low Curie temperature and a high temperature coefficient, which limits their application in motors and precision instruments with high ambient temperatures. Therefore, effectively solving the high-temperature stability of NdFeB has become the focus of many NdFeB magnet research works.
[0004] The heat resistance of a magnet refers to the fact that its magnetic properties do not deteriorate with increasing temperature. When NdFeB magnets are used at the heat source of a machine, it is required that the magnetic properties do not deteriorate with increasing operating temperature. In the prior art, NdFeB magnets with a low temperature coefficient have a lower operating temperature, lower coercive force and generally higher cost. At present, the method adopted by sintered NdFeB to improve the heat resistance of magnets is mainly to increase the Curie temperature by adding Co element. However, the addition of Co will form a soft magnetic grain boundary phase, which does not have a magnetic decoupling effect, resulting in a sharp decrease in the coercive force of the material. Compared with sintered NdFeB magnets, bonded NdFeB magnets have the advantages of high cost performance, easy molding and high processing precision. However, existing bonded NdFeB magnets have problems such as weak bonding between magnetic powder and special resin, incomplete resin coating on the surface of magnetic powder, and easy agglomeration, resulting in unsatisfactory high temperature resistance of the magnet.
[0005] The present invention introduces elements such as Y and Ni into the components of the NdFeB magnet to increase the Curie temperature of the magnet and reduce the temperature coefficient; a synthetic heat-resistant polyurethane elastomer is used as a binder and calendered with the surface-modified magnetic powder to achieve good compatibility, so that the prepared NdFeB magnet can still maintain high magnetic properties at a high temperature, and the process is simple and the cost is low. Summary of the invention
[0006] The technical problems solved by the present invention are:
[0007] In view of the deficiencies in the prior art, the present invention provides a method for preparing a NdFeB magnet, which solves the problems of low Curie temperature and poor heat resistance of the prior NdFeB magnet.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing a neodymium iron boron magnet, the preparation method being carried out according to the following steps:
[0010] (1) 10-15 parts by mass of metal Nd powder, 1-6 parts by mass of metal Y powder, 1.5-4.5 parts by mass of metal Pr powder, 2.5-3.5 parts by mass of metal Nb powder, 45-60 parts by mass of metal Fe powder, 8-18 parts by mass of metal Ni powder, 3-8 parts by mass of ZrO2, 0.6-5.4 parts by mass of B-Fe alloy, 0.2-1.5 parts by mass of metal Cu powder and 0.5-3.0 parts by mass of Al2O3 are placed in a water-cooled copper crucible of a vacuum arc melting furnace, and argon gas is introduced for protection. The crucible is heated to a vacuum degree of 0.8×10 -3 Pa-1.5×10 -3 Pa, smelting at a temperature of 1300-1500℃ for 10-30min, cooling into an alloy ingot, then breaking the alloy ingot into 8-15mm, placing it in a copper crucible of a melt rapid quenching furnace to melt, and quickly pouring the molten alloy liquid onto a molybdenum roller to obtain a NdFeB rapid quenching thin strip.
[0011] (2) Add the NdFeB quenched thin strip into a stainless steel hydrogen explosion tank and place it in a vacuum of 1.8×10 -1 Pa-2.8×10 -1 Pa, activation at a temperature of 450-550°C for 20-50min, absorbing hydrogen for 1-3h at a tank pressure of 0.15-0.25MPa, releasing hydrogen for 4-8h at a temperature of 480-520°C, cooling, and air flow grinding into fine powder with a particle size of 1-5μm to obtain NdFeB magnetic powder.
[0012] (3) Place the NdFeB magnetic powder in an ethanol solution of KH550, perform ultrasonic dispersion treatment at 20-35°C for 20-40 minutes, then soak for 12-24 hours, and dry at 100-120°C for 5-10 hours to obtain modified NdFeB magnetic powder.
[0013] (4) Add a heat-resistant polyurethane elastomer binder, a plasticizer, a lubricant and a calcium zinc stabilizer into a kneader, pre-treat at 140-170°C for 30-60 minutes, and then place in a closed mixer, add modified NdFeB magnetic powder for mixing, the top bolt pressure on the internal mixer is 0.4-0.9MPa, and the uniformly mixed material is calendered on a double-roll calender to obtain a heat-resistant NdFeB magnet.
[0014] Preferably, in step (1), the surface linear speed of the molybdenum roller is 5-20 m / s, and the belt spinning temperature is 1200-1350°C.
[0015] Preferably, the mass of KH550 in step (3) is 3-6% of the mass of NdFeB magnetic powder.
[0016] Preferably, in step (4), the substances are calculated by weight as follows: 2.5-6.5 parts of heat-resistant polyurethane elastomer, 0.5-1.5 parts of plasticizer, 2-4 parts of lubricant, 0.2-0.6 parts of calcium zinc stabilizer, and 85-95 parts of modified NdFeB magnetic powder.
[0017] Preferably, in step (4), the mixing temperature is 150-180°C, the mixing time is 40-80 min, and the roller temperature is 120-160°C.
[0018] Preferably, the preparation method of the heat-resistant polyurethane elastomer is carried out according to the following steps: vacuum dehydrating polytetramethylene ether diol at 100-130°C for 1-3h, then cooling to 40-60°C, adding 1,5-naphthalene diisocyanate, and keeping warm at 70-85°C for 2-3h to obtain a polyurethane prepolymer, then vacuum degassing for 5-10min, adding chain extenders 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 1,4-dioxane, stirring for 10-20min, pouring into a flat mold coated with a release agent, and obtaining a heat-resistant polyurethane elastomer after curing and drying.
[0019] Preferably, the substances are calculated by weight: 100 parts of polytetramethylene ether diol, 42-105 parts of 1,5-naphthalene diisocyanate, and 20-30 parts of the chain extender 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine.
[0020] Preferably, the curing temperature is 60-80° C., and the curing time is 5-10 days; the drying temperature is 110-130° C., and the drying time is 2-4 hours.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) Composition optimization: By introducing appropriate amounts of Y, Ni and other elements, the combination of magnet elements is optimized, the Curie temperature and coercive force of NdFeB magnets are significantly improved, the temperature coefficient is reduced, and the magnetic properties of the magnets themselves are maintained, further improving the shortcomings of NdFeB magnets' poor heat resistance and expanding the scope of application of NdFeB magnets.
[0023] (2) Process optimization: The rapid quenching thin-strip process can refine the main phase grains and evenly distribute the neodymium-rich phase, making the decoupling effect on the main phase grains more complete, thereby improving the coercive force of the magnet; the hydrogen explosion powder making process can obtain particles with a particle size of 1-5μm, reduce the oxidation of the magnet surface, and thus obtain a well-oriented magnet; the calendering molding process is used to make the magnetic powder present a sheet-like flat arrangement in both the parallel and perpendicular calendering directions, achieving mechanical orientation and thus having higher magnetic properties.
[0024] (3) Optimization of magnetic powder surface modification: The surface of NdFeB magnetic powder is modified by KH550. After dehydration and condensation, it forms a Si-O-covalent bond and chemically adsorbs the magnetic powder. This adsorption is tightly combined with the magnetic powder, has a good anti-oxidation effect and is beneficial to improving the adhesion between the magnetic powder and the resin.
[0025] (4) Optimization of heat-resistant polyurethane elastomer binder: By synthesizing polyurethane elastomers containing heat-resistant naphthyl and triazine groups, a very stable and rigid system is formed with the modified NdFeB magnet, which makes the magnet have excellent dimensional stability in high temperature environment. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Preparation of heat-resistant NdFeB magnets:
[0028] (1) 10-15 parts by weight of metal Nd powder, 1-6 parts by weight of metal Y powder, 1.5-4.5 parts by weight of metal Pr powder, 2.5-3.5 parts by weight of metal Nb powder, 45-60 parts by weight of metal Fe powder, 8-18 parts by weight of metal Ni powder, 3-8 parts by weight of ZrO2, 0.6-5.4 parts by weight of B-Fe alloy (containing 20-30 wt % of B), 0.2-1.5 parts by weight of metal Cu powder, and 0.5-3.0 parts by weight of Al2O3 are placed in a water-cooled copper crucible of a vacuum arc melting furnace, and argon gas is introduced for protection. The crucible is heated to a vacuum degree of 0.8×10 -3 Pa-1.5×10 -3 Pa, smelting at a temperature of 1300-1500℃ for 10-30min, cooling into an alloy ingot, then breaking the alloy ingot into 8-15mm, placing it in a copper crucible of a melt rapid quenching furnace to melt, and quickly pouring the molten alloy liquid onto a molybdenum roller with a surface linear speed of 5-20m / s and a strip throwing temperature of 1200-1350℃ to obtain a NdFeB rapid quenching thin strip.
[0029] (2) Add the NdFeB quenched thin strip into a stainless steel hydrogen explosion tank and place it in a vacuum of 1.8×10 -1 Pa-2.8×10 -1 Pa, activation at a temperature of 450-550°C for 20-50min, absorbing hydrogen for 1-3h at a tank pressure of 0.15-0.25MPa, releasing hydrogen for 4-8h at a temperature of 480-520°C, cooling, and air flow grinding into fine powder with a particle size of 1-5μm to obtain NdFeB magnetic powder.
[0030] (3) The NdFeB magnetic powder is placed in an ethanol solution of KH550 with a mass fraction of 3-6%, and is subjected to ultrasonic dispersion treatment at 20-35°C for 20-40 minutes, and then immersed for 12-24 hours, and dried at 100-120°C for 5-10 hours to obtain modified NdFeB magnetic powder.
[0031] (4) 100 parts by mass of polytetramethylene glycol are vacuum dehydrated at 100-130°C for 1-3h, then cooled to 40-60°C, 42-105 parts of 1,5-naphthalene diisocyanate are added, and the mixture is kept warm at 70-85°C for 2-3h to obtain a polyurethane prepolymer, which is then vacuum degassed for 5-10min, 20-30 parts of chain extenders 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 1,4-dioxane are added, stirred for 10-20min, and poured into a flat mold coated with a release agent, cured at 60-80°C for 5-10 days, and dried at 110-130°C for 2-4h to obtain a heat-resistant polyurethane elastomer adhesive.
[0032] (5) Add 2.5-6.5 parts by mass of a heat-resistant polyurethane elastomer binder, 0.5-1.5 parts by mass of a plasticizer, 2-4 parts by mass of a lubricant and 0.2-0.6 parts by mass of a calcium zinc stabilizer into a kneader, pre-treat at 140-170°C for 30-60 minutes, then place in a closed mixer, add 85-95 parts of modified NdFeB magnetic powder and mix, the mixing temperature is 150-180°C, the mixing time is 40-80 minutes, the roller temperature is 120-160°C, the top bolt pressure on the internal mixer is 0.4-0.9 MPa, and the uniformly mixed material is calendered on a double-roll calender to obtain a heat-resistant NdFeB magnet.
[0033] Example 1
[0034] (1) 12 parts by weight of metal Nd powder, 1 part of metal Y powder, 3.5 parts of metal Pr powder, 3 parts of metal Nb powder, 56 parts of metal Fe powder, 8 parts of metal Ni powder, 4.5 parts of ZrO2, 0.6 parts of B-Fe alloy (containing 25 wt% B), 0.6 parts of metal Cu powder, and 2.6 parts of Al2O3 were placed in a water-cooled copper crucible of a vacuum arc melting furnace, and argon gas was introduced for protection. The crucible was heated to a vacuum degree of 1.2×10 -3 Pa, smelting at 1350℃ for 20min, cooling into alloy ingot, then breaking the alloy ingot into 10mm, placing it in a copper crucible of a melt rapid quenching furnace to melt, and quickly pouring the molten alloy liquid onto a molybdenum roller with a surface linear speed of 15m / s and a strip throwing temperature of 1300℃ to obtain a NdFeB rapid quenching thin strip.
[0035] (2) Add the NdFeB quenched thin strip into a stainless steel hydrogen explosion tank and place it in a vacuum of 2.2×10 -1 Pa, activated at a temperature of 500°C for 40 minutes, absorbed hydrogen for 2 hours at a tank pressure of 0.2MPa, released hydrogen for 5 hours at a temperature of 510°C, cooled, and air flow ground into a fine powder with a particle size of 2μm to obtain NdFeB magnetic powder.
[0036] (3) The NdFeB magnetic powder was placed in an ethanol solution of KH550 with a mass fraction of 5%, and ultrasonically dispersed at 30°C for 35 minutes, then immersed for 16 hours, and dried at 110°C for 8 hours to obtain modified NdFeB magnetic powder.
[0037] (4) 100 parts by mass of polytetramethylene glycol were vacuum dehydrated at 120°C for 3 hours, then cooled to 45°C, 78 parts of 1,5-naphthalene diisocyanate were added, and the mixture was kept at 80°C for 2 hours to obtain a polyurethane prepolymer, which was then vacuum degassed for 10 minutes. 25 parts of chain extenders 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 1,4-dioxane were added, stirred for 15 minutes, and poured into a flat mold coated with a release agent. The mixture was cured at 70°C for 9 days and dried at 130°C for 3 hours to obtain a heat-resistant polyurethane elastomer adhesive.
[0038] (5) 2.5 parts by mass of a heat-resistant polyurethane elastomer binder, 1.2 parts by mass of a plasticizer phthalate, 3 parts by mass of a lubricant fatty amide and 0.5 parts by mass of a calcium zinc stabilizer were added to a kneader, pretreated at 160°C for 50 min, and then placed in a closed mixer, 90 parts by mass of a modified NdFeB magnetic powder were added and mixed. The mixing temperature was 170°C, the mixing time was 60 min, the roller temperature was 150°C, the top bolt pressure on the internal mixer was 0.6 MPa, and the uniformly mixed material was calendered on a double-roll calender to obtain a heat-resistant NdFeB magnet.
[0039] Example 2
[0040] The difference between this embodiment and embodiment 1 is that the amount of metal Y powder used in step (1) is 2 parts, and other conditions remain unchanged.
[0041] Example 3
[0042] The difference between this embodiment and embodiment 1 is that the amount of metal Y powder used in step (1) is 3 parts, and other conditions remain unchanged.
[0043] Example 4
[0044] The difference between this embodiment and embodiment 1 is that the amount of metal Y powder used in step (1) is 4 parts, and other conditions remain unchanged.
[0045] Example 5
[0046] The difference between this embodiment and embodiment 1 is that the amount of metal Y powder used in step (1) is 5 parts, and other conditions remain unchanged.
[0047] Example 6
[0048] The difference between this embodiment and embodiment 1 is that the amount of metal Y powder used in step (1) is 6 parts, and other conditions remain unchanged.
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that metal Y powder is not added in step (1), and other conditions remain unchanged.
[0051] Curie temperature test:
[0052] The Curie temperature and coercivity temperature coefficient of the magnets were tested using a vibrating sample magnetometer (VSM).
[0053]
[0054] The critical temperature at which a strong ferromagnetic material changes from ferromagnetism or ferrimagnetism to paramagnetism is called the Curie temperature. The higher the Curie temperature, the higher the working temperature of the material, and it is beneficial to improve the temperature stability of the magnetic material. From the test results in the above table, it can be seen that with the increase of the Y element content in the NdFeB alloy, the Curie temperature of the magnet rises from 289°C to 364°C, an increase of 75°C, indicating that the addition of the Y element improves the high-temperature working stability of the NdFeB magnet and significantly broadens the application range of the NdFeB magnet; the coercive force temperature coefficient refers to the ratio of its coercive force to temperature change, and the smaller the absolute value of the coefficient, the better the magnetic properties of the magnet; the data in the above table show that with the increase of the Y element content, the coercive force temperature coefficient changes from -0.3598% / °C in Comparative Example 1 to -0.1675% / °C in Example 6, which indicates that the addition of the Y element effectively improves the heat resistance of the NdFeB magnet, so it can be used in a wider temperature range.
[0055] Example 7
[0056] The difference between this embodiment and embodiment 1 is that the amount of metal Ni powder used in step (1) is 11 parts, and other conditions remain unchanged.
[0057] Example 8
[0058] The difference between this embodiment and embodiment 1 is that the amount of metal Ni powder used in step (1) is 14 parts, and other conditions remain unchanged.
[0059] Example 9
[0060] The difference between this embodiment and embodiment 1 is that the amount of metal Ni powder used in step (1) is 16 parts, and other conditions remain unchanged.
[0061] Example 10
[0062] The difference between this embodiment and embodiment 1 is that the amount of metal Ni powder used in step (1) is 18 parts, and other conditions remain unchanged.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 1 is that metal Ni powder is not added in step (1), and other conditions remain unchanged.
[0065] Magnetic properties test:
[0066] The vibrating sample magnetometer (VSM) was used to test the magnetic properties of the samples and obtain magnetic parameters such as coercivity and remanence.
[0067]
[0068] Coercivity represents the ability of magnetic materials to resist demagnetization. In the use of magnets, the higher the coercivity of the magnet, the better the temperature stability. From the test results in the above table, it can be seen that with the increase of Ni content in NdFeB alloy, the coercivity of the magnet gradually increases, indicating that the heat resistance of the magnet is improved to a certain extent; the remanence of NdFeB magnets increases slightly with the increase of Ni content, indicating that the addition of Ni does not affect the magnetic properties of the magnet.
[0069] Embodiment 11
[0070] The difference between this embodiment and embodiment 1 is that the amount of heat-resistant polyurethane elastomer binder used in step (5) is 3.5 parts, and other conditions remain unchanged.
[0071] Example 12
[0072] The difference between this embodiment and embodiment 1 is that the amount of heat-resistant polyurethane elastomer binder used in step (5) is 4.5 parts, and other conditions remain unchanged.
[0073] Example 13
[0074] The difference between this embodiment and embodiment 1 is that the amount of heat-resistant polyurethane elastomer binder used in step (5) is 5.5 parts, and other conditions remain unchanged.
[0075] Embodiment 14
[0076] The difference between this embodiment and embodiment 1 is that the amount of heat-resistant polyurethane elastomer binder used in step (5) is 6.5 parts, and other conditions remain unchanged.
[0077] Comparative Example 3
[0078] The difference between this comparative example and Example 1 is that no heat-resistant polyurethane elastomer binder is added in step (5), and other conditions remain unchanged.
[0079] Temperature resistance dimensional stability test:
[0080] The heat-resistant dimensional stability test of the magnet was carried out in an oven. The magnet to be tested was placed in an oven at 120° C. for 72 hours, and the volume change rate of the magnet was calculated.
[0081]
[0082] High temperature resistance is an important indicator of whether a magnet can work for a long time in a high temperature environment. If the high temperature resistance is poor, the magnet will age, expand, and decompose, resulting in a significant change in the size of the magnet, a decrease in the magnetic field strength, and the device cannot work. From the test results in the above table, it can be seen that with the increase in the content of heat-resistant polyurethane elastomer binder in the magnet, the volume change rate of the magnet gradually decreases after being dried in a 120°C oven for 72 hours, and it has better high temperature stability. This is because the polyurethane elastomer has both the high elasticity of rubber and the high strength of plastic, as well as excellent heat resistance and wear resistance. The introduction of naphthyl and triazine groups with good heat resistance makes the prepared binder have excellent high temperature resistance. After being modified with KH550, the NdFeB magnet can form a strong binding force with polyurethane, thereby further improving the heat resistance of the magnet.
[0083] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a neodymium iron boron magnet, characterized in that: The preparation method is carried out according to the following steps: (1) 10-15 parts by mass of metal Nd powder, 1-6 parts by mass of metal Y powder, 1.5-4.5 parts by mass of metal Pr powder, 2.5-3.5 parts by mass of metal Nb powder, 45-60 parts by mass of metal Fe powder, 8-18 parts by mass of metal Ni powder, 3-8 parts by mass of ZrO2, 0.6-5.4 parts by mass of B-Fe alloy, 0.2-1.5 parts by mass of metal Cu powder and 0.5-3.0 parts by mass of Al2O3 are placed in a water-cooled copper crucible of a vacuum arc melting furnace, and argon gas is introduced for protection. The crucible is heated to a vacuum degree of 0.8×10 -3 Pa-1.5×10 -3 Pa, smelting at a temperature of 1300-1500°C for 10-30min, cooling to form an alloy ingot, then breaking the alloy ingot into 8-15mm, placing it in a copper crucible of a melt rapid quenching furnace for melting, and quickly pouring the molten alloy liquid onto a molybdenum roller to obtain a NdFeB rapid quenching thin strip; (2) Add the NdFeB quenched thin strip into a stainless steel hydrogen explosion tank and place it in a vacuum of 1.8×10 -1 Pa-2.8×10 -1 Pa, activation at a temperature of 450-550°C for 20-50min, absorbing hydrogen for 1-3h at a pressure of 0.15-0.25MPa in the tank, releasing hydrogen for 4-8h at a temperature of 480-520°C, cooling, and air flow grinding into fine powder with a particle size of 1-5μm to obtain NdFeB magnetic powder; (3) placing the NdFeB magnetic powder in an ethanol solution of KH550, dispersing it with ultrasound at 20-35°C for 20-40 minutes, then soaking it for 12-24 hours, and drying it at 100-120°C for 5-10 hours to obtain modified NdFeB magnetic powder; (4) Add the heat-resistant polyurethane elastomer binder, plasticizer, lubricant and calcium zinc stabilizer into a kneader, pre-treat at 140-170°C for 30-60 minutes, then place in a closed mixer, add modified NdFeB magnetic powder for mixing, the top bolt pressure on the mixer is 0.4-0.9MPa, and the mixed material is calendered on a double-roll calender to obtain a heat-resistant NdFeB magnet; The preparation method of the heat-resistant polyurethane elastomer binder in step (4) is carried out according to the following steps: vacuum dehydrating polytetramethylene ether diol at 100-130°C for 1-3h, then cooling to 40-60°C, adding 1,5-naphthalene diisocyanate, and keeping warm at 70-85°C for 2-3h to obtain a polyurethane prepolymer, and then vacuum degassing for 5-10min, adding chain extender 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine and 1,4-dioxane, stirring for 10-20min, pouring into a flat mold coated with a release agent, and curing and drying to obtain a heat-resistant polyurethane elastomer binder; The weight percentage of each substance is as follows: 100 parts of polytetramethylene glycol, 42-105 parts of 1,5-naphthalene diisocyanate, and 20-30 parts of chain extender 2,4,6-tris(4-hydroxyphenyl)-1,3,5-triazine; In step (3), the mass of KH550 is 3-6% of the mass of NdFeB magnetic powder; In step (4), the weight percentage of each substance is 2.5-6.5 parts of heat-resistant polyurethane elastomer and 85-95 parts of modified NdFeB magnetic powder; In the step (4), the mixing temperature is 150-180°C, the mixing time is 40-80 minutes, and the roller temperature is 120-160°C; in the preparation method of the heat-resistant polyurethane elastomer adhesive, the curing temperature of the curing and drying is 60-80°C, and the curing time is 5-10 days; the drying temperature of the curing and drying is 110-130°C, and the drying time is 2-4 hours.
2. The method for preparing a NdFeB magnet according to claim 1, wherein: In the step (1), the surface linear speed of the molybdenum roller is 5-20 m / s, and the belt spinning temperature is 1200-1350°C.
3. The method for preparing a NdFeB magnet according to claim 1, characterized in that: In step (4), the substances are calculated by weight: the plasticizer is 0.5-1.5 parts, the lubricant is 2-4 parts, and the calcium zinc stabilizer is 0.2-0.6 parts.
Citation Information
Patent Citations
High-performanceradialorientation rare-earth permanent magnetic tube and thermal-deformationforming method thereof
CN106887293A
Method of preparing high-performance neodymium iron boron magnet by terbium powder
CN110233039A